Physiological interpretation of heart rate variability spectral analysis data - Чиж, М.О. (Fiziol. Zh. 2019; 65(2): 31-42., 2019)
Despite the widespread use of the spectral analysis of heart rate variability (HRV) in biology and medicine, today questions about the physiological interpretation of frequency ranges remain unsolved. The combined recording of the electrocardiogram and registration of the amplitude and frequency of displacement of the chest during breathing allowed us to estimate the contribution of the act of breathing on HRV in the HF range and to determine the leading role of mechanical contraction of the diaphragm in the formation of respiratory arrhythmia. We also determined experimentally that, depending on the frequency and strength of the mechanical effect on the aorta of animals, it is possible to obtain corresponding peaks in the spectrogram. In humans, a test with swallowing at varying the frequency of swallowing allows obtaining a peak in any area of the spectrogram. The results obtained with the contraction of the muscles of the anterior abdominal wall indicate the effect of a rhythmic increase in intra-abdominal pressure on the formation of the spectrum. Based on the obtained results, we can assume that the peaks in the LF-range, not related to the arterial pressure waves, are due to the mechanical effect on the aorta of the peristaltic waves of the digestive tract organs. The results of studies, conducted when changing the position of the body in space, showed that hydrodynamic changes in the venous system largely determine the very slow-wave component of the spectrum.
Chizh N.A. Physiological interpretation of heart rate variability spectral analysis data. Fiziol. Zh. 2019; 65(2): 31-42.
Keywords: spectral analysis; heart rate variability; physiological interpretation